2016
DOI: 10.1111/jir.12312
|View full text |Cite
|
Sign up to set email alerts
|

‘What vision?’: experiences of Team members in a community service for adults with intellectual disabilities

Abstract: The perceived absence of a vision for the service, combined with a dominant culture viewed by its members as strongly focussed on bureaucracy and process, potentially compromises the ability of these CTs to respond proactively to the needs of people with IDs. Given the changes in legislation, policy and practice that have taken place since CTs were established, it would be timely to revisit their role and purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Implementing change poses challenges to service providers, families and people with intellectual disabilities (Brown, Anand, Fung, Isaacs, & Baum, ; Jones & Gallus, ). Trusting relationships and effective communication among stakeholders are required for positive change management in disability services during the transition to community living (Clare et al, ; Schalock, Verdugo, Bonham, Fantova, & Loon, ). Others argue that the move away from congregated settings requires a local, individualised approach for people with intellectual disabilities and support staff combined with a much broader societal shift in recognising full citizenship of people with intellectual disabilities (Bigby & Fyffe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Implementing change poses challenges to service providers, families and people with intellectual disabilities (Brown, Anand, Fung, Isaacs, & Baum, ; Jones & Gallus, ). Trusting relationships and effective communication among stakeholders are required for positive change management in disability services during the transition to community living (Clare et al, ; Schalock, Verdugo, Bonham, Fantova, & Loon, ). Others argue that the move away from congregated settings requires a local, individualised approach for people with intellectual disabilities and support staff combined with a much broader societal shift in recognising full citizenship of people with intellectual disabilities (Bigby & Fyffe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many such teams were developed following deinstitutionalisation to facilitate the delivery of services to people with intellectual disability with or without comorbidities and to provide specialist expertise to meet their healthcare needs. 10 In several areas, such teams undertook the acute and medium- to long-term management of behaviours that challenge and/or mental ill health in the community. There are a plethora of terms such as ‘peripatetic teams’, ‘assertive outreach teams’ and ‘specialist behaviour teams’ that have been used to describe ISTs.…”
Section: Specialist Supportmentioning
confidence: 99%
“…In a later literature review, Slevin et al (2008) concluded that CLDTs were responsible for providing highly specialist treatment (i.e., for challenging behaviour, mental health problems and complex health needs) (Hassiotis et al, 2000;Roy et al, 2000), supporting professionals in primary healthcare settings to meet individuals' needs, liaising with local providers to coordinate services, facilitating access to healthcare services, and providing educational and advisory support to individuals and those supporting them. However, there has been no known comprehensive empirical evaluation to date examining the roles and responsibilities of CLDTs, thus further indicating our understanding of the internal mechanisms of these teams is extremely limited (Clare et al, 2017).…”
Section: Community Services In the Uk For People With Learning Disabimentioning
confidence: 99%
“…Much of the literature suggests CLDTs need to be clear and transparent in their roles, responsibilities, and service coordination at all levels (Hudson, 1995). A multi-disciplinary, multi-agency approach appears to be preferred, where the teams are locally accessible, cohesive, supportive of their members, effective in their performance, and adopt a person centred approach to care planning with service user involvement (Clare et al, 2017;Hudson, 1995;McKenzie et al, 2000;Slevin et al, 2008). Practical suggestions include the provision of specialist clinical psychology and psychiatry services for those with complex needs (e.g., mental health problems, challenging behaviour, contact with the criminal justice system), accessible information packs, a keyworker system, clear eligibility criteria, small caseloads (i.e., 10-15 service 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 users), the capacity to deliver intensive support (e.g., through daily visits), and out of hours operation (Hudson, 1995;McKenzie et al, 2000;Shepherd, 1998).…”
Section: Best Practice Guidelines For Cldtsmentioning
confidence: 99%